Stunting dan Kebijakan Pangan dan Gizi di Indonesia - Maliati, Nulwita (Program Magister Administrasi Publik, 2023)
The nutritional development of the Indonesian people is not getting better. Many nutritional problems occur and cannot be overcome. Stunting (short toddlers) illustrates the existence of chronic nutritional problems. In general, this research aims to analysis some researches about stunting as one indicator that shows the problem in children growth and analyze national policies on food and nutrition in Indonesia. The methode that is used in this article is literature review that collected some stunting researches and food and nutrition policies that made by the Indoensian government. Nutritional status is influenced by the household's ability to provide adequate food, child care patterns, knowledge of nutrition and maternal health, access to health services, and other socio-cultural factors. National policies on food and nutrition in Indonesia are also developing in accordance with the development of nutrition science and problems. The principle 4 sehat 5 sempurna which began in 1952 and was updated with the program that is called Guidelines for Balanced Nutrition. Various programs to address food and nutrition problems have been made but nutrition problems have not been successfully resolved. Based on the principle of food sovereignty, there needs to be community empowerment based on knowledge and local food resources. Efforts to handle malnourished and habituation of healthy and nutritious food must be carried out in food consumption according to local knowledge so that it is easily applied by the community. Further research is important to analyse local knowledge and stakeholders that involve in food fullfillment in family and community.